Wooden doors with paintings of Musicians - Temples of India Project Team (Jio Institute, 2024)
The doorways/long windows punctuating the walls of the mandapa (pillared hall) in the Bhandasar Temple are seen here. The wooden doors have paintings of musicians. The arch above the doorway has paintings of Tirthankara Rishabnath’s life. A band above the arch depicts stories about forbidden things in Jain traditions.